Proof‐of‐Principle Experiment of the Pseudorandom Multiplexing of White‐Pump Light for Spectral Photothermal Microscopy. Issue 9 (13th August 2020) - Seto, Keisuke; Yamada, Hiromu; Kobayashi, Takayoshi; Tokunaga, Eiji
Abstract: Absorption spectroscopy, coupled with photothermal super‐resolution microscopy, is enabled by the frequency division multiplexing of the pump‐light (Pu) wavelength whose spectral component is discriminated by the modulation frequency. This demonstrates a great advantage in availing multicolor image information. However, the response gain of the thermal lens signal to the spectral components is not uniform because of the limited relaxation rate of the thermal lens, i.e., the gains of the components assigned to the high‐frequency modulations are diminished, thus resulting in a distorted absorption spectrum. In this study, white‐pump light (Pu) is multiplexed by pseudonoise sequences (PNSs) to avoid the distortion. The frequency bandwidth of the PNSs is equalized, and the gains of the thermal lens generation to the respective wavelength components are balanced. The obtained results indicate that the modulation‐waveform deformation due to the slow responses of the sample can also distort spectra. To mitigate the problem, the countermeasures required to compensate for this distortion are also discussed. Abstract : Multiplexing is demonstrated, employing the pseudonoise sequences (PNSs) for discrimination of a constituent wavelength in white continuum light, to explore the feasibility of photothermal spectroscopy. The multiplexed white‐pump light (Pu) generates a thermal lens; the thermal lens is detected by the probe light (Pr), and the absorption spectrum is measured by demultiplexing of Pr, employing PNSs for Pu.